Eruption of Metastatic Paraganglioma After Successful Therapy with (177)Lu/(90)Y-DOTATOC and (177)Lu-DOTATATE - Wolf, Katherine I. (Nucl Med Mol Imaging, 2019)
ABSTRACT: Metastatic paraganglioma treatment options are limited. Peptide receptor radionuclide therapy (PRRT) has been introduced as a novel management option for metastatic neuroendocrine tumors demonstrating safety, efficacy, and increased quality of life. We present two cases of marked progression of metastatic paraganglioma following initial partial response to PRRT. Given their positivity on (68)Ga-DOTATATE PET/CT and (111)In-octreotide SPECT, they underwent PRRT. Imaging following treatment revealed significant improvement in size and intensity, with some foci nearly completely resolved in one patient, and disease regression with a decrease in the number and size of bone and liver lesions in the second patient. Within months, repeat imaging in both patients revealed extensive metastatic disease with new lesions, which eventually lead to their deaths. The mechanism for rapid disease progression after partial response is not well understood, although it could be related to initially high Ki-67 levels or (18)F-FDG PET/CT SUV(max) values. However, naturally rapid disease progression despite PRRT response cannot be excluded. This finding warrants the importance of proper patient counseling along with early and accurate pre-PRRT assessment, taking into consideration the above potential risk factors for therapy response in order to personalize treatment regimens and achieve maximum patient benefit. CLINICALTRIALS.GOV IDENTIFIER: NCT00004847